Upaya Badan Pengurus Daerah dalam Meningkatkan Kinerja Pelayanan Majelis Gereja Kemah Injil Indonesia Kecamatan Kelam Permai Kabupaten Sintang - Evendi, Yuliono Evendi (Jurnal Kala Nea, 2020)
Abstract: Local Church Leaders are one component of spiritual leaders who are responsible for church growth, specifically among the Gospel Tabernacle Church of Indonesia in Sintang Regional West Kalimantan. The aims of this study is to examine and describe the efforts that have been made by the Sintang Regional Gospel Tabernacle Church Indonesia Management in improving the performance of the services of the local church leaders in the district Kelam Permai. The method in this research is an explanatory sequential and then arranges the results to explan the more detail with qualitative reasearch. The samples are Local Church Leader of Dait Kelam Permai, Genezaret Kebong and Karunia SP 7 Sepan Lebang purposively selected. All local church leaders in these 3 churches have received training and guidance from Sintang Regional of Gospel Tabernacle Church of Indonesia Management. Data collection techniques are through observation, quesionnaires, and interviews. Data is collected and analyzed quantitativly, through the relative frequency distribution table, dan described qualitatively. The results showed that, 12 local church leaders from the Gospel Tabernacle Church Indonesia of Dait Kelam Permai have the ability to carry out their duties and functions, 14 local church leaders in Genezaret Kebong can carry out their duties and functions, 7 local church leaders in Karunia SP 7 Sepan Lebang can carry out their duties and funtions properly. All the knowledge and skills possessed by local church leaders in these 3 churches are the real impact of all the efforts made by the Sintang Regional Gospel Tabernacle Church of Indonesia Management. The efforts made by the Gospel Tabernacle Church Indonesia of Sintang Regional Management are providing seminars and training, mentoring, preparing supporting facilities and infrastructure, and coordinating, communicating and evaluating the services of local church leaders.